Program of Emotion Management Training for 4th Grade Students of SD Kemala Bhayangkari 1 Medan - Clarencia, Graceia; Hani, Tsabitah; Siahaan, Nadya Odetta; Mumtaz, Farhani Amanda; Ramadhani, Raisya Putri; Selima, Ulya Fachira; Nasution, Arrowva Nafsyah; Dharma, Annisa Iqlima Ade; Supriyantini, Sri (ARZUSIN, 2026)
Although emotion regulation has been widely examined in previous studies, research specifically evaluating the effectiveness of emotion regulation training for elementary school students in Indonesia, particularly in private schools emphasizing discipline and character development such as SD Kemala Bhayangkari 1 Medan, remains limited. This study aimed to evaluate the effectiveness of emotion regulation training for students at SD Kemala Bhayangkari 1 Medan. A quantitative approach with a pre-experimental one-group pre-test post-test design was employed, involving 21 fourth-grade students selected through convenience sampling. Data were collected using pre-test and post-test measures and analyzed using the Wilcoxon Signed-Rank Test with JASP software. The findings indicate no significant difference between students’ pre-test and post-test scores. This result does not necessarily indicate that the training was ineffective; rather, students’ pre-test scores were already in the good category, limiting the potential for measurable improvement after the intervention. The study concludes that emotion regulation remains important in strengthening students’ ability to understand, recognize, and adaptively manage their emotions. These findings contribute to the development of school-based psychological intervention literature, particularly in relation to emotion regulation among elementary school children. Practically, the study provides insights for educational institutions, teachers, and psychologists in designing emotion regulation training that is better aligned with students’ initial emotional competence. Future research should examine the long-term effectiveness of emotion regulation training and its potential impact on students’ academic achievement.